HUBUNGAN KONSUMSI JUNK FOOD DAN MEDIA INFORMASI TERHADAP MENARCHE DINI PADA REMAJA PUTRI DI DESA HUTA LOMBANG KECAMATAN LUBUK BARUMUN - Rina Marlina Hutasuhut; Fauji Haryati Tamba (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Early menarche is menstruation that arrives earlier between 10-11 years. A biological sign of menarche is sexual maturity. In women who experience early menarche, their reproductive function is as rapid as that of adult women. said that the age of menarche for adolescent girls has shifted to a younger age, namely 10-11 years, but normally menarche in girls occurs at the age of 12 - 16 years with an average age of 13 years. The aim of this research is to3 find out the relationship between consumption of junk food and information media on early menarche in Puri teenagers in Huta Lombang village, Lubuk Barumun subdistrict. This research is descriptive analytical in nature which aims to find out a picture of the reality of the object studied objectively regarding the relationship between junk consumption. food and information media on early menarche in adolescent girls in Huta Lombang village, Lubuk Barumun subdistrict. This research was conducted starting in July with a population of 63 and a sample of 63 respondents and sampling using the Simple Random Total Sampling technique using a questionnaire. Data management by means of editing, coding, tabulating and data entry. Research results: the majority of menarche is early consumption, 40 (63.5%) consume junk food very often, 42 (66.7%) information media, 43 (68.3%), research results on the relationship between junk consumption food against early menarche obtained (OR) 0.105. 95% CI=0.022-0.510 and P value 0.004<0.05, the relationship between information media and early menarche was obtained (OR) = 6.129. 95% CI=1.842-19.543 and P value 0.003 <0.05. Young women in particular maintain a balanced diet and reduce consumption of junk food which has an impact on early menarche by maintaining a nutritious and natural diet and reducing access to information media and seeing positive and more useful things in the media.